Microstructure effects on process outputs in micro scale milling of heat treated Ti6Al4V titanium alloys - Ahmadi, Masoud; Karpat, Yiğit; Acar, Ozgun; Kalay, Yunus Eren (Journal of materials processing technology, 2018)
This study investigates the influence of materials’ microstructural characteristics, including grain size and phase fractions, in micro end milling of heat treated Ti6Al4V titanium alloys. Micro milling process conditions such as feed, depth of cut, and the cutting edge radius of the micro end mill are in the same order of magnitude as the grain size of the material, which gives rise to the anisotropic behavior of the multiphase materials and their deformation characteristics considering their grain size, grain boundaries, and phase fractions. A good understanding of such relationships is believed to be instrumental in developing predictive models of machining based on computational techniques. The influence of micro milling process on the crystallographic texture and microstructure of Ti6Al4V alloys is the subject of this study. For this purpose, heat treatment was performed on the Ti6Al4V samples to obtain two different microstructures: fine equiaxed and enlarged equiaxed microstructures. Micro milling experiments were performed on each sample and process outputs such as cutting forces, areal surface texture, built-up edge (BUE) formation, and alterations in the microstructure were investigated. Electron backscatter diffraction (EBSD) analysis was used to investigate the microstructure of the machined surfaces. It was observed that smaller grain size (both α and β) and lower fraction of β phase in the material yielded higher cutting forces. BUE formation and its size were affected by the microstructure of the samples. The results of this study may be useful in developing microstructure-based, predictive modeling of micro milling process.